Sistem Peradilan Adat Nagari di Sumatera Barat (Jurnal Bina Praja, 2019)
The state recognizes and respects indigenous and tribal people and their traditional rights insofar as they are alive and in accordance with the development of society and the principles of the Unitary State of the Republic of Indonesia, as contained in Article 18 B paragraph 2 of the 1945 Constitution. However, the fulfillment of cultural identity and the rights of indigenous people have not been maximized. This study aims to find the conceptual model of the Customary Justice system in an effort to protect the existence of the rights of indigenous people to build the strength of civil society in West Sumatra. This research uses research and development methods. Data retrieval is done by survey, observation, interview, and Focus Group Discussion (FGD) methods. This study found that; 1) Minangkabau people have their own local wisdom in resolving customary disputes, even for a broader range of life issues, long before Indonesia was found, 2) Nagari Customary Justice system is a translation of Customary Limbago which is the life philosophy of Minangkabau people, 3) Nagari Customary Judicial institutional structure is a representation of the existence of the tribe in the Nagari, so that its cultural legitimacy becomes strong. And, 4) the Nagari Customary Justice system is an effort to build the sovereignty of civil society, namely an autonomous, independent, egalitarian, and democratic society. It is hoped that the results of this study will be a guideline in establishing the Nagari Customary Justice institution in West Sumatra.